ENTERPRISE REVOLVING FUNDS AND REVOLVING MONEY - Egamberdiyev Shavkatbek; Akbarov Shokirjon (Лучшие интеллектуальные исследования, 2024)
Annotation: This article provided various information on the working capital and circulating money of the enterprise. A lot of literature has been studied on the rotary backgrounds of the enterprise, analysis has been carried out on circulating money. The proposal to increase the working capital and working capital of the enterprise was given conclusions.